Attenuation of delay-period activity of monkey prefrontal neurons by an alpha2-adrenergic antagonist during an oculomotor delayed-response task - Sawaguchi, T (Journal of neurophysiology, 1998)
To examine the role of norepinephrine receptors in spatial working memory processes mediated by the prefrontal cortex (PFC), noradrenergic antagonists (yohimbine for alpha2, prazosin for alpha1, and propranolol for beta receptors) were applied iontophoretically to neurons of the dorsolateral PFC in rhesus monkeys that performed an oculomotor delayed-response (ODR) task. The ODR task was initiated when the monkeys fixated on a central spot on a computer monitor and consisted of fixation (1 s), cue (1 of 4 peripheral cues, 0.5 s), delay (fixation cue only, 4 s), and go periods. In the go period, the subject made a memory-guided saccade to the target location that was cued before the delay period. I focused on 49 neurons that showed directional delay-period activity, i.e., a sustained increase in activity during the delay period, the magnitude of which varied significantly with the memorized target location. Iontophoretic (usually 50 nA) application of yohimbine, but not prazosin or propranolol, significantly decreased the activities of most of the neurons with directional delay-period activity (n = 41/49, 81%). Furthermore, yohimbine attenuated the sharpness of tuning, examined by a tuning index, of delay-period activity and had a greater attenuating effect on delay-period activity than on background activity. These findings suggest that the activation of alpha2-adrenergic receptors in the dorsolateral PFC plays a modulatory role in neuronal processes for visuospatial working memory.